THE DEVELOPMENT OF MAOS HAND WRITING BATIK WITH DIPONEGORO WAR STORIES MOTIF FOR DRESS - Ayasofia, Addina Aufa; Santoso, Ratna Endah (Arty: Jurnal Seni Rupa, 2021)
The Maos Cilacap batik motif was once used as a code in the Diponegoro War. There has been no development of a motif using the story of the Diponegoro War so that the history of Maos batik is not widely known. Until now, the development of Maos batik motifs is still limited to the original motifs which are added with motifs from other natural potentials. The purpose of this development is to develop Batik Maos designs by combining original motifs with the narrative motifs of the Diponegoro War stories so as to produce Batik Maos products which can be a means of education about the history of their origins. The method used consists of the design method with Collin Clipson theory, design concepts, and visualization. The results of this development include: (1) The design is carried out by displaying the original Maos batik motif combined with the visualization of the Diponegoro war story with stylized and naturalist styles, where in one fabric design containing one original maos batik motif is collaborated with the visualization of the Diponegoro war story which is in tune with the meaning of the original motif when into a war code. From development 8 designs were successfully created with the distribution of motifs according to the types of batik in Maos, namely geometry, flora and fauna. (2) This development is carried out by designing a direct motif on the ready-to-wear clothing pattern, namely the dress so that it can be ensured that the visualization of the Diponegoro war story is not cut into pieces when it becomes a form of clothing.